Facile construction of ternary ZnO/CdS/GO heterostructure with boosting and stable photocatalytic performance towards organic dyes degradation. (3rd July 2022) - Pan, Yusong; Yin, Minyuan; Fang, Hongjun; Xu, Linfeng; Yan, Haixian; Pan, Chengling
ABSTRACT: A novel ternary ZnO/CdS/GO heterostructure with boosting photocatalytic performance and stability was prepared by a simple hydrothermal method. The morphology, crystal structure, chemical composition and optical properties of the composite were thoroughly investigated. Results show that the obtained ZnO/2CdS/10GO composite exhibits the optimal activity towards RhB removal under sunlight irradiation, which is higher than that of pristine ZnO and CdS. The enhanced photocatalytic performance of the composite is attributed to the close heterostructure and excellent conductivity of GO. Besides, the radical trapping experiments revealed that superoxide radical ( O2 − ) and holes (h + ) were the vital active species in the photocatalytic process. Meanwhile, the corresponding photocatalytic mechanism was also investigated. In all, this work supplies a facile route to design highly efficient and stable photocatalysts for water purification.